KERJASAMA INDONESIA DAN REPUBLIK RAKYAT TIONGKOK (RRT) MELALUI LOCAL CURRENCY SETTLEMENT (LCS) - Mario Rizki; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Local Currency Settlement (LCS) is a cooperative scheme for the use of local currency in direct trade and investment transactions. The main goal is to reduce dependence on the US dollar and the adverse effects of that dependence. Indonesia first established LCS cooperation, namely with Malaysia and Thailand in 2016 and Japan in 2019. Indonesia continues to expand this LCS cooperation partnership, namely with the People's Republic of China (PRC) in 2020. It is important to see why Indonesia continues to expand its LCS partnership, namely with China which is Indonesia's newest partner. This study aims to analyse the purpose of Indonesia in establishing LCS cooperation with China.In order to analyse the problem, the researcher uses the International Cooperation Theory, the LCS concept, and the level of analysis of the nation-state. The research method used by the research is descriptive qualitative and the data obtained are primary data obtained from documents from the official website of Bank Indonesia and the Ministry of Trade of the Republic of Indonesia and secondary data obtained from books, journals, and newspapers.The results of this study indicate that the reason for Indonesia establishing SCS cooperation with China is because China is Indonesia's main trading partner and Indonesia wants to expand the use of the rupiah, reduce dependence on the US dollar, Indonesia wants to achieve the vision of the Blueprint Pengembangan Pasar Uang (BPPU) 2025 and to implement the National Economic Recovery (PEN) program in response to the COVID-19 pandemic.Keywords: Local Currency Settlement, US Dollar Domination, Bank Indonesia.